2021
DOI: 10.14569/ijacsa.2021.0121217
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Feature Selection Algorithms in Sentiment Analysis for Drug Reviews

Abstract: Social media data contain various sources of big data that include data on drugs, diagnosis, treatments, diseases, and indications. Sentiment analysis (SA) is a technology that analyses text-based data using machine learning techniques and Natural Language Processing to interpret and classify emotions in the subjective language. Data sources in the medical domain may exist in the form of clinical documents, nurse's letter, drug reviews, MedBlogs, and Slashdot interviews. It is important to analyse and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Drug reviews can also be described as an individual's impressions regarding several drug-related fields, such as efficacy, adverse effects, convenience, and value [14]. These reviews offer abundant data that can be utilised to make informed decisions concerning public health and medication safety [20].…”
Section: B Drug Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug reviews can also be described as an individual's impressions regarding several drug-related fields, such as efficacy, adverse effects, convenience, and value [14]. These reviews offer abundant data that can be utilised to make informed decisions concerning public health and medication safety [20].…”
Section: B Drug Reviewsmentioning
confidence: 99%
“…This section presents related studies on sentiment analysis of drug reviews. Table I shows an extended summary of related studies based on the techniques used in the sentiment analysis of drug reviews [20].…”
Section: Related Workmentioning
confidence: 99%
“…Chen et al (2019) employed fuzzy-rough feature selection and TF-IDF vectorizer to conduct opinion mining on the drug reviews, which resulted in improving the classification accuracy as well as the run time. Furthermore, Ahmad et al (2021) presented different feature extracting methods that were implemented in previous studies on drug review data. The review showed that the metaheuristic algorithm showed superior results to the machine learning approach for feature extraction purposes.…”
Section: Related Workmentioning
confidence: 99%